Agresivitas pada komunitas suporter Lamasea: Bagaimana peran fanatisme dan persepsi kekalahan? - Faizal Aditya Putra; Amanda Pasca Rina; Sahat Saragih (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between fanaticism and the perception of defeat with aggressiveness in the Lamasea community supporters. This research is a quantitative research using correlational research. The subjects in this study were 85 Lamasea community supporters. The data collection method was carried out through distributing questionnaire links online using the Google form. The data analysis technique used in this study is multiple regression. Based on the results of the data analysis that has been carried out, it shows that there is a significant difference between the variables Fanaticism and the perception of defeat towards aggressiveness with a correlation coefficient= 0.533 with sig = 0.000 (<0.05). Keywords: Fanaticism, Perception of defeat, Aggressiveness